ANALISIS PROSES AFIKSASI PADA LIRIK LAGU FEBY PUTRI DALAM ALBUM RIUH - I Gede Esa Ananda; I Wayan Simpen; Ni Putu N. Widarsini (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Abstract: This research is entitled "Affixation to the lyrics of Feby Putri's song in the album Riuh: Morphological Study". This research aims to describe (a) the types of affixations in the lyrics of Feby Putri's song in the album Riuh, and (b) the morphophonemic and morphosyntactic structure of the affixes in the lyrics of Feby Putri's song in the album Riuh. This type of research is qualitative research with the data source in the form of song lyrics. The data collection methods and techniques used in this research are the observation method with note-taking techniques, the data analysis methods and techniques used are the agih method with basic techniques in the form of techniques for direct elements, as well as the methods and techniques for presenting the results of data analysis in the form of formal, informal methods with techniques. descriptive. The results of this research include the types of affixations, morphophonemic and morphosyntactic structure of the affixes found in the lyrics of the song Feby Putri in the album Riuh, which are as follows. The types of affixation found amounted to 100 data with the following details. Prefixation amounted to 73 data, suffixation amounted to 9 data, confixation amounted to 3 data, and joining affixation amounted to 17 data. In this data, no infixation was found. The morphophonemic and morphosyntactic structures found are as follows. Morphophonemics were found based on changes, additions and deletions of phonemes (ng) totaling 23 data. Morphosyntax was found based on the form and type of word, 50 data of word form and 100 data of word type. Keywords:morphology, affixation, Feby Putri song lyrics, Riuh album, morphophonemics, and morphosyntax